IMPACT OF CLUSTERS ON ECONOMIC ACTIVATION OF TOURISM REGIONS - Gancarczyk, Jacek (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of the article is to present the concept of economic activation of tourism regions based on the development of enterprise clusters and on the development of small and medium sized enterprises (SMEs). The following topics are discussed: reasons for the current interest in clusters, approaches to the cluster phenomenon by different researchers and proposed definitions of the cluster, examples of regional clusters and sources of their competitiveness. Moreover, the contribution of SMEs into the regional economy is outlined. Finally, the function of clusters in the policy for economic activation of the region and for the regional SME policy was proposed. The article is based on the review of the literature in industrial clusters and on the results of empirical studies.